A novel chairside technique to assess the interocclusal clearance and abutment axial walls during tooth preparation - Aryen Kaushik; Aditya Chaudhary; Punit R. S Khurana (Wolters Kluwer Medknow Publications, 2023)
The importance of a judicious and unerring abutment tooth preparation in the field of prosthodontics has always been paramount. It is not uncommon for many clinicians to face challenges during laboratory fabrication of fixed prostheses, caused due to inappropriate occlusal clearance and over axial wall taper of the abutment tooth. With evolving technologies and methods, the modus operandi for attaining such tooth preparation is varying; however, every technique has its own shortcomings. The technique mentioned in the article is cost-effective as it uses modified Heister mouth gag forceps to achieve the desired objective of evaluating the prepared abutment morphology three-dimensionally with minimum chairside time.